2021
DOI: 10.1111/and.13858
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin and fucoidan prevent apoptosis and reducing ER stress in diabetic rat testes

Abstract: Sitagliptin increases the levels of incretin hormones and stimulates a decrease in blood glucose levels, by blocking the DPP4 enzyme. We have very limited information about impact of sitagliptin on male genital system and relationship between sitagliptin/diabetes/ER. Fucoidan can be effective in blood glucose homeostasis. We goal to explain of the effect of sitagliptin and introduce an approach of fucoidan treatment in experimental diabetes in male rats. Fifty‐eight Wistar albino rats were divided into C‐contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
(52 reference statements)
0
18
0
Order By: Relevance
“…This also agrees with previous study [ 8 ], which detected the implication of the apoptosis signaling in the hippocampus of the VaD model. Kizilay et al [ 66 ] attributed the initiation of apoptosis pathways to the existence of oxidative stress. However, STG supplementation resulted in a significant reduction of the percentage of degenerated neurons compared with the VaD group values.…”
Section: Discussionmentioning
confidence: 99%
“…This also agrees with previous study [ 8 ], which detected the implication of the apoptosis signaling in the hippocampus of the VaD model. Kizilay et al [ 66 ] attributed the initiation of apoptosis pathways to the existence of oxidative stress. However, STG supplementation resulted in a significant reduction of the percentage of degenerated neurons compared with the VaD group values.…”
Section: Discussionmentioning
confidence: 99%
“…Forty 6-week-old male Sprague Dawley rats (weighing 160-180 g) were provided by the animal center of the first affiliated hospital of Xinxiang medical college, China. Rats were injected intraperitoneally with 60 mg/kg streptozotocin (STZ, sigma Aldrich Corporation, St. Louis, Mo, USA) [31], followed by 60 mg/kg for another 2 consecutive days, and the random blood glucose concentration in tail vein was no less than 16.67 mmol/L for two times. According to the guidelines of the first affiliated hospital of Xinxiang medical college, the animals were housed in a 12 h light/dark cycle at 21 ± 3 o C, and relative humidity 30-70%.…”
Section: Animal Modelmentioning
confidence: 99%
“…SIT also significantly decreased CHOP mRNA and protein expression, which serves as an apoptotic modulator, meaning hyperactivation of ER stress. Until now, there has been limited reports on impact of SIT on ER stress ( Bachor et al, 2015 ; Yuzbasioglu et al, 2018 ; Kizilay et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our results demonstrated that SIT significantly decreased expressions of IRE1α, GRP78, and CHOP in the aorta from the hyperlipidemic rats and in PA-treated HUVECs. SIT was effective in reducing apoptosis by decreasing the expression of caspase 3, caspase 12, GRP78, CHOP in the ER stress pathway ( Kizilay et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%